Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x(y-z) + y(z-x) + z(x-y)
= xy - xz + zy - xy + xz - yz
= ( xy - xy ) - ( xz - xz ) + ( zy - yz )
= 0 - 0 + 0
= 0 ( đpcm )
b) x(y+z-yz) - y(z+x-xz) + z(y-x)
= xy + xz - xyz - yz - xy + xyz + zy - zx
= ( xy - xy ) + ( xz - zx ) - ( xyz - xyz ) - ( yz - zy )
= 0 + 0 - 0 - 0
= 0 ( đpcm )
\(B=-x^2-10y^2+6xy-2x+10y-3\)
\(=-x^2-9y^2-1+6xy-2x+6y-y^2+4y-4+2\)
\(=-\left(x-3y+1\right)^2-\left(y-2\right)^2+2\le2\)
Dấu \(=\)khi \(\hept{\begin{cases}x-3y+1=0\\y-2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=5\\y=2\end{cases}}\).
a: \(2x^3+x^2-13x+6\)
\(=2x^3-4x^2+5x^2-10x-3x+6\)
\(=\left(x-2\right)\left(2x^2+5x-3\right)\)
\(=\left(x-2\right)\left(2x^2+6x-x-3\right)\)
\(=\left(x-2\right)\left(x+3\right)\left(2x-1\right)\)
b: \(2x^2+y^2-6x+2xy-2y+5=0\)
\(\Leftrightarrow x^2+2xy+y^2+x^2-4x+4-2x-2y+1=0\)
\(\Leftrightarrow\left(x+y\right)^2+\left(x-2\right)^2-2\left(x+y\right)+1=0\)
\(\Leftrightarrow\left(x-2\right)^2+\left(x+y-1\right)^2=0\)
=>x-2=0 và x+y-1=0
=>x=2 và y=-1
a=1-2x
bạn có thể trình bày cụ thể hơn được ko